Analysis Of Job Satisfaction Of Generation Z Employees In Kendal District - Sari, Indah Tika; Efriyani Sumastuti; Rr Hawik Ervina (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study examines the factors influencing job satisfaction among Generation Z employees in Kendal Regency, focusing on work-life balance, workload, work stress, work environment, and social support. A quantitative approach was employed, using a purposive sampling method to gather data from 100 respondents. The data were analyzed through multiple linear regression using SPSS. The findings reveal that workload and social support significantly enhance job satisfaction, indicating that employees who receive adequate support and manageable workloads are more satisfied with their jobs. Conversely, work-life balance, work stress, and the work environment did not have a significant impact on job satisfaction, suggesting that these factors might play a lesser role for Generation Z employees in the context of this study. This research highlights the need for organizations to focus on optimizing workload and strengthening social support systems to improve job satisfaction among younger employees, while further investigation is needed for other variables.